Ustawodawstwo w dziedzinie podatków - Rutkowska, Anna (Legislation in the Field of Taxation, 2005)
International agreements place a duty on (each) government to comply on their own territory certain standards and methods of procedure. Inculcated within the Polish community, regulations connected to entry into the European Community, in the area of Union legislation, direct taxation in relation to the proof of profits an organisation and also tied in, with mattes, as well as a united system of taxation. It has application in the casa of mergers, shares, entry of members, exchange of contributions in connection with partnerships of the different governments of the membership States.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 108-115